THE EFFECTIVENESS OF BENSON RELAXATION THERAPY AND GUIDED IMAGERY THERAPY ON ANXIETY OF PRE-OPERATIVE SECTIO CAESAREA PATIENTS AT THE REGIONAL GENERAL HOSPITAL IN 2024 - Faruq, Lingga Abduh; Hardiyani, Tati (Jurnal Keperawatan, 2025)
Anxiety that occurs before Sectio Caesarea surgery is a natural thing, arising from facing something that has been or has never been experienced before. Therefore, an action is needed that can reduce the patient's anxiety level. Benson relaxation and Guided imagery therapy are two therapeutic non-pharmacological therapeutic measures that can be used to reduce the patient anxiety levels. This study aims to determine the effectiveness of Benson relaxation and Guided imagery therapy on anxiety of pre-operative Sectio Caesarea patients at The Regional General Hospital. This study was conducted from February to March 2024 at Ajibarang Regional Hospital with the population in this study being all pre-operation sectio casaera patients at Ajibarang Regional Hospital, Ajibarang, Central Java. This study used a quantitative method, with a cross-sectional design. The sample in the study was 32 respondents who were taken by purposive sampling and then divided into two intervention groups with 16 respondents each for each intervention group. The data collection in this study is in the form of observations, interviews, and questionnaires. Data analysis using Paired sample t-test. The results showed that there was a significant effect between Benson relaxation therapy and Guided imagery therapy on the anxiety levels in pre-operative Sectio Caesarea patients (p<0.001).